Outcome of transformed follicular lymphoma worsens according to the timing of transformation and to the number of previous therapies. A retrospective multicenter study on behalf of Fondazione Italiana Linfomi (FIL). (21st February 2019) - Rusconi, Chiara; Anastasia, Antonella; Chiarenza, Annalisa; Marcheselli, Luigi; Cavallo, Federica; Rattotti, Sara; Botto, Barbara; Ferrari, Angela; Nassi, Luca; Pagani, Chiara; Meli, Erika; Arcaini, Luca; et al.
Summary: Optimal treatment for transformed follicular lymphoma (tFL) is not fully defined. Clinical characteristics and treatments that impact on post‐transformation outcome of 176 biopsy‐proven tFL were analysed. Transformation occurred at initial diagnosis in 52% (Group 1) and after a FL diagnosis in 48% (Group 2). Five‐year overall survival was 84% for Group 1 and 51% for Group 2 ( P < 0·001). In Group 1, 5‐year progression‐free survival was superior after rituximab maintenance compared to observation only (94% vs. 53%, P = 0·024). In Group 2, an inverse trend was found between survival and both a higher number of pre‐transformation treatment lines and a short time‐to‐transformation.